Critical Analysis of Guidelines for the Implementation of Religious Moderation in Islamic Education Institutions - Fahruddin, Ahmad Hanif; Nurhayati, Ifa; Rahman, Mufiqur; Luciana , Luciana; Yusuf, Yusuf (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
The high level of publication of religious moderation is not directly proportional to the strengthening of radicalism in Indonesia. Religious moderation has become a public discourse, especially since the publication of the decision of the Directorate General of Islamic Education Number 7272 of 2019 concerning Guidelines for the Implementation of Religious Moderation in Islamic Education. This research analyzes the decision of the directorate general of Islamic Education Number 7272 of 2019. The research method uses a qualitative approach with the type of library research, namely the note-taking technique. This research shows that several guidelines need to be discussed again. Firstly, lesson plan administration is not required to include indicators of religious moderation learning. Secondly, the unique material on religious moderation does not stand alone but is only presented substantively. Third are teachers' human resource competencies in religious moderation, especially components. School. Fourth, the character of Islamic boarding schools in terms of accommodation for religious moderation. Publication of religious moderation, in particular at public universities.